Effect of hydrocortisone on outcome of septic shock patients. A prospective observational study in a tertiary care ICU. - Hassan, Muahmmad Rauf-ul-; Aslam, Seemal; Waseem, Muhammad; Bashir, Imran; Naz, Shafia; Iqbal, Ahtesham (Pakistan Journal of Medical & Health Sciences, 2022)
Introduction: Sepsis and septic shock have 10% and 40% mortality in ICU respectively. Early recognition and prompt management of septic shock in ICU can reduce mortality. Further, some studies have suggested that hydrocortisone can impact outcome of septic shock significantly. Methodology: We designed prospective observational study to evaluate the effect of hydrocortisone in septic shock patients. Septic shock was defined according to definition proposed by international consensus definition of septic shock 2016. We excluded those who were less than 18 years and receiving steroids for some other indication at the time of admission to ICU. Primary outcome was to determine mortality in ICU. Secondary outcome was to evaluate length of stay, vasopressor days, vasopressor free days and dose of norepinephrine. Results: We studied 208 cases of septic shock. Median age was 61 years. Out of 208 participants, 106 received hydrocortisone. Out of 102 cases who did not receive hydrocortisone, 56.7% died and 42.3% survived (p=<0.001). There was no effect of hydrocortisone on length of stay, vasopressor days, vasopressor free days (OR: 0.7,0.3,1.1), (p=0.98,0.92,0.93) respectively. Conclusion: We concluded that hydrocortisone reduces mortality in septic shock patients in ICU.